1992: Keep peace by pooling armies. (1st November 2020) - Forsberg, Randall
ABSTRACT: Peace researcher Randall Forsberg shares her plan to take advantage of the end of the Cold War to rethink armed forces, military spending, and arms exports. She proposes that countries reduce nuclear and conventional forces, adopting limited militaries that could participate in multilateral peacekeeping operations should the need arise but could not engage in offensive war.